THE ROLE OF ACTION GAMES IN THE FORMATION OF PHYSICAL QUALITIES AND TECHNICAL-TACTICAL SKILLS - Hamrokulov Rasul Abdusattorovich; Mukhammadov Nomoz (Journals Park Publishing, 2023)
Effective performance and high results in volleyball can only be achieved through well-developed physical qualities. In this regard, endurance quality, including game endurance and jumping endurance, is particularly important.
Keywords: Many years of sports training, active games, special endurance , strengthening of health , correct development of the child physically (weight, body and body parts sizes, living capacity of the country, etc.) , formation of vital movement skills (walking, running, jumping, stopping, pulling, etc.)